Microdeletions including YWHAE in the Miller–Dieker syndrome region on chromosome 17p13.3 result in facial dysmorphisms, growth restriction, and cognitive impairment. Issue 12 (6th July 2009) - Sreenath Nagamani, S C; Zhang, F; Shchelochkov, O A; Bi, W; Ou, Z; Scaglia, F; Probst, F J; Shinawi, M; Eng, C; Hunter, J V; Sparagana, S; Lagoe, E; et al.
Abstract : Background: Deletions in the 17p13.3 region are associated with abnormal neuronal migration. Point mutations or deletion copy number variants of the PAFAH1B1 gene in this genomic region cause lissencephaly, whereas extended deletions involving both PAFAH1B1 and YWHAE result in Miller–Dieker syndrome characterised by facial dysmorphisms and a more severe grade of lissencephaly. The phenotypic consequences of YWHAE deletion without deletion of PAFAH1B1 have not been studied systematically. Methods: We performed a detailed clinical and molecular characterization of five patients with deletions involving YWHAE but not PAFAH1B1, two with deletion including PAFAH1B1 but not YWHAE, and one with deletion of YWHAE and mosaic for deletion of PAFAH1B1 . Results: Three deletions were terminal whereas five were interstitial. Patients with deletions including YWHAE but not PAFAH1B1 presented with significant growth restriction, cognitive impairment, shared craniofacial features, and variable structural abnormalities of the brain. Growth restriction was not observed in one patient with deletion of YWHAE and TUSC5, implying that other genes in the region may have a role in regulation of growth with CRK being the most likely candidate. Using array based comparative genomic hybridisation and long range polymerase chain reaction, we have delineated the breakpoints of these nonrecurrent deletions and show that the interstitial genomic rearrangements are likely generated by diverse mechanisms, including the recently described Fork Stalling and Template Switching (FoSTeS)/Microhomology Mediated Break Induced Replication (MMBIR). Conclusions: Microdeletions of chromosome 17p13.3 involving YWHAE present with growth restriction, craniofacial dysmorphisms, structural abnormalities of brain and cognitive impairment. The interstitial deletions are mediated by diverse molecular mechanisms.